2006
DOI: 10.1007/s11527-005-9040-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bitumen and aggregate composition on stripping in bituminous mixtures

Abstract: The impact of bitumen and aggregate composition on stripping was investigated using four bitumens and four aggregates. Moisture sensitivity was assessed based on retained resilient modulus and tensile strength ratio (MRR and TSR, respectively). The results indicate that mixtures from the bitumen with a high acid number exhibited high resilient modulus and tensile strength in the dry condition for all the aggregates. In wet condition, this conclusion did also hold except for one aggregate. Regarding penetration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…e surface tension of the liquid is caused by its surface molecules suffering unbalanced force, and usually varied with the temperature [21]. According to the surface tension experiment, the relationship between surface tension of asphalt and temperature can be expressed as equation (2).…”
Section: Variation Of Asphalt Parameters With the Temperaturementioning
confidence: 99%
See 1 more Smart Citation
“…e surface tension of the liquid is caused by its surface molecules suffering unbalanced force, and usually varied with the temperature [21]. According to the surface tension experiment, the relationship between surface tension of asphalt and temperature can be expressed as equation (2).…”
Section: Variation Of Asphalt Parameters With the Temperaturementioning
confidence: 99%
“…Water damage is mainly derived from the loss of the bonding between asphalt and aggregates, which is closely related to the viscosity and cohesion of asphalt, the alkalinity or acidity property, and the surface roughness of aggregates. Some authors demonstrated that moisture could damage the asphalt that lost in strength and durability due to the presence of water [1][2][3]. Now, the mechanism of bonding between asphalt and aggregates has become the hottest topic currently, and lots of researches have been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Marshall stability, compressive strength, shear strength etc. [5][6][7]. The optimal A-A ratio is regarded as a density design criterion, which is evaluated by the air void of whole mixture in the volumetric design of super-pave [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…The interaction process between asphalt pavement and water was the following: leaching of water, infiltrating of the road surface water into the pavement surface layer under the dynamic pressure, and moisturizing of groundwater (Petersen and Plancher, 1998;Cheng et al, 2003;Bagampadde et al, 2004;Bagampadde et al, 2006;Bagampadde and Kiggundu, 2007;Burak and Emine, 2007;Airey, 2008;Saeed, 2009). The chemical constituents in asphalt cement (AC) concrete could be leached in wet weather (Peter et al, 2001).…”
Section: Introductionmentioning
confidence: 99%